IMPLIKASI BRAND EXPERIENCE TERHADAP BRAND TRUST DAN BRAND LOYALTY PADA COFFEE SHOP DI SURABAYA - Fabiola Leoparjo; Irra Chrisyanti Dewi; Otje Herman Wibowo (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to examine the influence of brand experience on brand trust and brand loyalty among coffee shops in Surabaya. The research employs a quantitative method using questionnaire distribution to 115 coffee shop consumers in Surabaya. SEM-PLS analysis reveals that brand experience has a positive and significant impact on building customer trust and loyalty. These findings provide an important foundation for business owners to develop marketing strategies focused on enhancing customer experience quality to strengthen brand relationships.